2010
DOI: 10.1177/1091581810380147
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Deposition of the Insect Repellent DEET and the Sunscreen Oxybenzone From Repeated Topical Skin Applications in Rats

Abstract: Insect repellent N,N-diethyl-m-toluamide (DEET) and sunscreen oxybenzone are capable of enhancing skin permeation of each other when applied simultaneously. We carried out a cellular study in rat astrocytes and neurons to assess cell toxicity of DEET and oxybenzone and a 30-day study in Sprague-Dawley rats to characterize skin permeation and tissue disposition of the compounds. Cellular toxicity occurred at 1 µg/mL for neurons and 7-day treatment for astrocytes and neurons. DEET and oxybenzone permeated across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 39 publications
2
28
1
1
Order By: Relevance
“…Considerable tissue distribution of the compounds indicated that the parent compounds had not been fully metabolized after 24 h. Disposition of oxybenzone in both liver and kidney was larger than that of DEET, possibly due to its lower clearance value and prolonged absorption from the skin depot. Liver concentrations of DEET and oxybenzone from combined topical application were significantly greater than those observed from intravenous and single topical administration, which was consistent with previous studies indicating permeation enhancement from concurrent application of the two test compounds . Although this study did not elucidate where DEET or oxybenzone was metabolized, the metabolism most likely occurred in the liver, as reports indicated that DEET was oxidized by the cytochrome P‐450 family of enzymes in rodent liver microsomes .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Considerable tissue distribution of the compounds indicated that the parent compounds had not been fully metabolized after 24 h. Disposition of oxybenzone in both liver and kidney was larger than that of DEET, possibly due to its lower clearance value and prolonged absorption from the skin depot. Liver concentrations of DEET and oxybenzone from combined topical application were significantly greater than those observed from intravenous and single topical administration, which was consistent with previous studies indicating permeation enhancement from concurrent application of the two test compounds . Although this study did not elucidate where DEET or oxybenzone was metabolized, the metabolism most likely occurred in the liver, as reports indicated that DEET was oxidized by the cytochrome P‐450 family of enzymes in rodent liver microsomes .…”
Section: Resultssupporting
confidence: 89%
“…For intravenous administration, solutions of DEET (0.3%, w/v) and oxybenzone (0.1%, w/v) were prepared using a mixture of Emulphor:ethanol:water (2:3:5, v/v/v). The study preparation was injected into the tail vein of the animals at 2 mg/kg of DEET (Group 1) or 2 mg/kg of oxybenzone (Group 2) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzophenone-3 was detected in plasma and urine after topical application of sunscreens (Fediuk et al, 2011(Fediuk et al, , 2010Janjua et al, 2008). Beyond compromising skin photoprotection, cutaneous penetration of UV-filters in viable skin layers can cause photosensitivity (Hanno et al, 2012) and increase the risk of toxic or allergic reactions (Yang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding toxicological findings, a low toxicity level associated to BZ3 after topical applications of cosmetic formulations in rats and mice has been found (Daston et al 1993;Okereke et al 1995;Fediuk et al 2010). Moreover, the in vitro estrogenic activity showed by various UV filters (Schlumpf et al 2001) has been also confirmed to MBC and 3BC under in vivo conditions .…”
Section: Iii2 Main Objectives Of the In Vivo Studiesmentioning
confidence: 83%